Ответы и объяснения

Лучший Ответ!
  • Участник Знаний
2014-01-26T10:26:14+04:00
Cos²(п/3 -7x) = 1/2
извлекаем корень из обеих частей
cos(п/3 -7x) = -/+ 1/√2

-1/√2   это  cos 3п/4, тогда
cos(п/3 -7x) =  cos 3п/4
с учетом периодичности функции косинус 2п
п/3 -7x =  3п/4 + 2пk  ,  k Є Z
7x = п/3 - 3п/4 - 2пk = -5п/12 - 2пk
x = - 5п/84 - 2пk/7  ,  k Є Z

или

1/√2   это  cos п/4, тогда
cos(п/3 -7x) =  cos п/4
с учетом периодичности функции косинус 2п
п/3 -7x =  п/4 + 2пk  ,  k Є Z
7x = п/3 - п/4 - 2пk = п/12 - 2пk
x = п/84 - 2пk/7  ,  k Є Z